AN ANALYTICAL EXPLORATION OF CAPITALISM AND CORRUPTION IN CARYL CHURCHILL’S SERIOUS MONEY - Bute, Amol; Pooja (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present paper explores Caryl Churchill’s Serious Money (1987) as a critical examination of capitalism and its inherent corruption. Set against the backdrop of 1980s Britain, a period marked by financial deregulation and neoliberal policies, the play critiques the morally corrosive effects of a profit-driven society. Through a detailed analysis of key themes such as greed, exploitation, and ethical compromise, this study argues that Serious Money exposes the dehumanizing impact of capitalism on individuals and institutions. The play’s portrayal of financial speculation, corporate manipulation, and the commodification of identity highlights how capitalism fosters moral decay, inequality, and systemic corruption. Additionally, the play’s fragmented structure, use of non-naturalistic techniques, and stylized language underscore the chaotic and alienating nature of capitalist systems. Ultimately, this paper contends that Serious Money is not only a critique of the 1980s financial boom but a timeless commentary on the corrupting forces of capitalism that continue to shape contemporary society.